Primary mucinous adenocarcinoma of the ureter and renal pelvis: A case report - Aparna A. N. Namshiker; Amala J. Kudchadker; R. G. Wiseman Pinto (Indian Journal of Pathology and Microbiology)
Primary adenocarcinoma rarely occurs in the upper urinary tract and accounts for less than 1% of the urothelial tumors. Here we present a case report of a 45-year-old female patient who presented with a lump in the abdomen and pain in the right lumbar region for 2 months. Various radiological investigations revealed right-sided hydronephrosis with enhancing masses in the right proximal ureter and renal pelvis associated with multiple calculi. A gross examination of the right nephrectomy specimen revealed multiple cystic areas filled with mucinous material and papillary projections in the renal pelvis. A necrotic growth was observed in the right proximal ureter in association with the staghorn calculus in the renal pelvis. Histological examination of the ureteric mass and solid areas from the renal pelvis showed acini and papillary projections lined by pseudostratified columnar epithelium showing malignant changes. Surrounding areas also revealed intestinal metaplasia with moderate to marked dysplasia in some places. The ureteric malignancy was observed to infiltrate the inner two-thirds of the wall of the ureteric muscular layer and extend until the margin of excision. Thus, a diagnosis of mucinous adenocarcinoma of the ureter and renal pelvis with intestinal metaplasia and dysplasia that occurred in association with a large staghorn calculus was made.